Modernisation Processes as Seen in Light of the Theory and Methodology - Pylypenko, V.,; Chepurko, G. (Социология: теория, методы, маркетинг, 2018)
The paper discusses theoretical and m ethodological perspectives on the study of modernisation processes, which is of great importance nowadays.